Access to healthcare services during incarceration among female inmates. Issue 4 (19th December 2016) - Ahmed, Rabia; Angel, Cybele; Martel, Rebecca; Pyne, Diane; Keenan, Louanne
Abstract : Purpose: Incarcerated women have a disproportionate burden of infectious and chronic disease, in addition to substance use disorder and mental health illness, when compared to the general population (Binswanger et al., 2009 ;Fazel et al., 2006 ; Fuentes, 2013;Kouyoumdjian et al., 2012 ). Women often enter the correctional system in poor health, making incarceration an opportunity to address health issues. The purpose of this paper is to explore the barriers to accessing health services that female inmates face during incarceration, the consequences to their health, and implications for correctional health services delivery. Design/methodology/approach: Focus groups were conducted in Canadian correctional center with female inmates. Focus groups explored women's experiences with accessing health services while incarcerated; the impact of access to health services on health during incarceration and in the community; and recommendations for improving access to health services. Thematic analysis was completed using N-vivo 10. Findings: The women described multiple barriers to accessing health services that resulted in negative consequences to their health: treatment interruption; health disempowerment; poor mental and physical health; and recidivism into addiction and crime upon release. Women made three important recommendations for correctional health service delivery: provision of comprehensive health entry and exit assessments; improvement of health literacy; and establishment of health support networks. The recommendations were organized into an "Accessing Health Services Resource Manual" for incarcerated women. Originality/value: There is a paucity of existing literature examining provision of health services for female inmates. These findings have relevancy for correctional and community health care providers and organizations that provide health services for this vulnerable population.